Woman, in Parts - dela Cruz, Noelle Leslie (Animo Repository, 2022)
In this essay, the text of a craft lecture presented for the Bienvenido Santos Creative Writing Center, I discuss the interrelationship between gender and poetry. I present a close-reading of “Dreamweavers” by Marjorie Evasco, followed by a recital and critical description of five of my own poems. These are organized around specific body parts, by way of critical engagement with the association between femininity and the body.